The Influence of Health Education on Peer Behavior with Bullying Incidents in Adolescents at the Education Foundation High School Medan Family in Medan City - Hayati, Nila; Mediastuti, Fitriani; Padinding, Siswanto (Jurnal EduHealth, 2023)
Bullying behavior still occurs in students at the Medan Family Education Foundation High School. Group mates (gangs) engage in bullying behavior towards friends and underclassmen such as yelling and taunting. One way to respond to bullying behavior can be realized in providing health education in schools. With health education in schools, students can be assisted with problems that are being faced during the learning and socialization process at school. The research objective was to analyze the effect of health education on peer behavior with the incidence of bullying in adolescents at the Medan Family Education Foundation High School in Medan City. The research design uses a quasi-experimental approach with a pre-post test design with control group approach. The population in this study were all young students at the Medan Family Education Foundation High School in Medan City as many as 480 students. The number of samples was 82 people consisting of 41 samples for the case group and 41 samples for the control group. The sampling technique is probability sampling with simple random sampling technique. Univariate data analysis with frequency distribution tables, bivariate analysis with t-test.There is an effect of health education on knowledge of bullying in adolescents at the Medan Family Education Foundation High School in Medan City with a p-value <α = 0.05, there is an effect of health education on bullying attitudes in adolescents at the Medan Family Education Foundation High School in Medan City with p-value < α = 0.05 and there is an effect of health education on bullying acts in adolescents at the Medan Family Education Foundation High School in Medan City with a p-value < α = 0.05. Health education affects peer behavior and can reduce the incidence of bullying in adolescents..